1994
DOI: 10.1523/jneurosci.14-12-07747.1994
|View full text |Cite
|
Sign up to set email alerts
|

Propofol modulates activation and desensitization of GABAA receptors in cultured murine hippocampal neurons

Abstract: Propofol (2,6 di-isopropylphenol) is an alkyphenol recently introduced for use as a general anesthetic. The modulation of GABAA receptor activation and desensitization by propofol was studied using a rapid perfusion system and whole-cell voltage-clamp recordings from mouse hippocampal neurons. The effects of concentrations of propofol used clinically on single-channel and synaptic currents were also examined. Propofol evoked current responses (EC50 = 61 microM) and shifted the dose-response curve of GABA-activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

28
150
2
4

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(184 citation statements)
references
References 41 publications
(55 reference statements)
28
150
2
4
Order By: Relevance
“…Our results would seem to be consistent with these latter findings, but whether this increase in synaptic strength in facilitating trains is attributable to a relief from postsynaptic receptor desensitization as at auditory synapses (Brenowitz and Trussell, 2001;Wong et al, 2003) is unclear. A slow desensitization of GABA A receptors during repetitive activation has been described in other systems (Orser et al, 1994;Jones and Westbrook, 1996;Overstreet et al, 2000) and could conceivably contribute to the depression observed here when P r is high. It is also equally plausible that, by blocking CB 1 receptors, we may be relieving an eCB-driven, Ca 2ϩ -dependent inhibition of release machinery (Hsu et al, 1996;Bellingham and Walmsley, 1999) that is recruited selectively during repetitive synaptic activation.…”
Section: Discussionsupporting
confidence: 60%
“…Our results would seem to be consistent with these latter findings, but whether this increase in synaptic strength in facilitating trains is attributable to a relief from postsynaptic receptor desensitization as at auditory synapses (Brenowitz and Trussell, 2001;Wong et al, 2003) is unclear. A slow desensitization of GABA A receptors during repetitive activation has been described in other systems (Orser et al, 1994;Jones and Westbrook, 1996;Overstreet et al, 2000) and could conceivably contribute to the depression observed here when P r is high. It is also equally plausible that, by blocking CB 1 receptors, we may be relieving an eCB-driven, Ca 2ϩ -dependent inhibition of release machinery (Hsu et al, 1996;Bellingham and Walmsley, 1999) that is recruited selectively during repetitive synaptic activation.…”
Section: Discussionsupporting
confidence: 60%
“…A similar phenomenon has been seen in experiments on chromaffin cells and dorsal root ganglion neurones (Robertson, 1989) with pentobarbitone and etomidate. More recently it has also been observed in experiments involving high concentrations of propofol in embryonic murine hippocampal neurones (Orser et al, 1994).…”
Section: Discussionmentioning
confidence: 79%
“…In addition, the general anaesthetic directly activates GABAA receptors at higher concentrations, relevant to total intravenous anaesthesia (Hales & Lambert, 1991;Hara et al, 1993;Orser et al, 1994). Numerous other compounds with general anaesthetic properties potentiate the actions of GABA and at higher doses directly activate GABAA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the post-operative dreams, mood disturbances, and hallucinations observed following propofol anaesthesia, are more commonly associated with the dissociative anaesthetic ketamine (Young, 1988;Suresh, 1991;Oxorn et al, 1994). Propofol also blocks several non-ligand gated channels and exerts opposing actions on excitatory and inhibitory neurotransmitter receptors (Frenkel & Urban, 1991;Hales & Lambert, 1992;Magnelli et al, 1992;Veintemilla et al, 1992;Wachtel & Wegrzynowicz, 1992, Baum 1993Hara et al, 1993;Dilger et al, 1994;Olcese et al, 1994;Orser et al, 1994). Modulation of these receptors might also contribute to the clinical properties of propofol.…”
Section: Discussionmentioning
confidence: 99%